2015
DOI: 10.1371/journal.pone.0121554
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Cute Infants Does Not Depend on Their Ethnicity or Species: Evidence from Hypothetical Adoption and Donation Paradigms

Abstract: Results of previous work suggest a preference of adult observers for cute compared to less cute infants. In Study 1 we investigated whether the preference for cute infants depends on the ethnicity and species of the infant. We simultaneously presented two faces (one cute and one less cute) and asked Caucasian participants to choose the infant to whom they would rather give a toy (Task 1) and which infant they would rather adopt (Task 2). The infants were Caucasian or African human babies or dog puppies. For al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…When presented with cute and less-cute infants, adults prefer to give a toy to or even adopt the cuter one [29]. Adults who see an infant face prior to a simple task have faster reaction times and sustain their engagement in the task [30].…”
Section: Fast Responses To Infantsmentioning
confidence: 99%
“…When presented with cute and less-cute infants, adults prefer to give a toy to or even adopt the cuter one [29]. Adults who see an infant face prior to a simple task have faster reaction times and sustain their engagement in the task [30].…”
Section: Fast Responses To Infantsmentioning
confidence: 99%
“…Evidence suggests that preference for infant features is independent of ethnicity (Alley, ; Chin, Wade, & French, ; Golle, Probst, Mast, & Lobmaier, ) and even species (Borgi, Cogliati‐Dezza, Brelsford, Meints, & Cirulli, ; Golle, Lisibach, Mast, & Lobmaier, ; Golle et al, ; Little, ). Golle et al () reported that participants were more willing to adopt and give a toy to cuter puppies and infants, regardless of the infant's ethnicity. Similarly, Chin found that infants with large eyes, a key characteristic of Kindchenschema, were considered cuter than infants with small eyes, regardless of ethnicity (Chin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Important to note is that baby schema seems to be a universal stimulus. On the one hand, because it appears in almost every mammal [28], and on the other hand, because the degree of baby schema in human adults or infants, cats and dogs modulates cuteness perception [37,3941]. Especially for women of reproductive age, newborns are extremely relevant stimuli, because their survival is directly linked to reproductive success.…”
Section: Introductionmentioning
confidence: 99%